Enhancing Asphalt Mix Performance through the Incorporation of Crumb - Herish Jaf; Asmaa Abdulmajeed Mamhusseini (Eurasian Journal of Science and Engineering)
The aim of this study is to evaluate the effects of incorporating crumb rubber as a modifier into asphalt mixtures and to achieve an improved blend for pavement applications. The study involved testing of hot mix asphalt samples through the Marshall method procedure. In total, 15 samples were meticulously prepared and tested to ascertain the Optimum Binder Content, which was determined to be 4.8%. Various tests of bitumen having PG 40/50 taken from a company in Sulaymaniyah City, are conducted to assess the quality and properties of bitumen. The study encompassed the incorporation of three distinct percentages of crumb rubber (10%, 20%, and 30% by weight of bitumen). A comprehensive comparative analysis was conducted between conventional and modified asphalt concrete mixtures, focusing on parameters such as Marshall Stability, Flow value, and other volumetric characteristics. Through a rigorous process involving the preparation of 25 samples, it was conclusively determined that 11.3% of crumb rubber content represents the most effective percentage for enhancing stability and flow characteristics within the asphalt concrete mix compared to the conventional results. The maintenance of an important balance between stability and flow is of utmost importance in the Marshall mix design process, as it guarantees that the asphalt mixture possesses the necessary durability to endure the load and movement of traffic without experiencing undue deformation.